2020
DOI: 10.1101/2020.08.09.243246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of COVID-19 Inhibitors Targeting the SARS-CoV2 Nsp13 Helicase

Abstract: The raging COVID-19 pandemic caused by SARS-CoV2 has infected millions of people and killed several hundred thousand patients worldwide. Currently, there are no effective drugs or vaccines available for treating coronavirus infections. In this study, we have focused on the SARS-CoV2 helicase (Nsp13), which is critical for viral replication and the most conserved non-structural protein within the coronavirus family. Using homology modeling and molecular dynamics approaches, we generated structural models of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
(70 reference statements)
0
18
0
Order By: Relevance
“…NSP13 Helicase is important for viral replication and proliferation ( White et al, 2020 ). The crystal structure of NSP13 Helicase (PDB ID: 6ZSL) was used for docking study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NSP13 Helicase is important for viral replication and proliferation ( White et al, 2020 ). The crystal structure of NSP13 Helicase (PDB ID: 6ZSL) was used for docking study.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we chose fifteen phytochemical molecules from flavonoids, flavins, terpenoids, steroids families ( Table 1 ) for our screening purpose, and performed blind docking between the selected phytochemicals and the reported crystal structures of the target proteins of SARS-COV-2 having important functions. The target proteins include nucleocapsid protein N-terminal RNA binding domain ( Kang et al, 2020 ), NSP15 Endoribonuclease ( Kim et al, 2020 ), Nsp9 RNA binding protein ( Sutton et al, 2004 ), Papain-like protease ( Shin et al, 2020 ), Nonstructural protein 10 (NSP10) ( Rogstam et al, 2020 ), NSP13 helicase ( White, Lin, & Cheng, 2020 ), main protease ( Jin et al, 2020 ) and RNA-dependent RNA polymerase (RdRp) ( Gao et al, 2020 ). We analysed for potential inhibitory activity through docking study for all fifteen phytochemicals and found that 1,3,6-Trigalloyl glucose, Beta-Sitosterol and Daucosterol possess most promising inhibitory effect against all eight SARS-CoV-2 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…We tested 56 drugs for colloidal aggregation that had been reported to be active in biochemical repurposing screens against SARS-CoV-2 18, 2730, 32, 38 ( SI Table 1 ). Five criteria were used to investigate whether reported hits formed colloidal aggregates: a. particle formation indicated by scattering intensity, b. clear autocorrelation curves, c. an MDH IC 50 in the micromolar – high nanomolar range, d. restoration of MDH activity with the addition of detergent, and less stringently e. high Hill slopes in the inhibition concentration response curves ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown CEP inhibits virus at entry and post-entry step [ 11 , 13 ]; however, the mechanisms of CEP’s antiviral activity after virus entry into cell remains unclear. Recent researches have demonstrated CEP also strongly inhibits nonstructural protein (Nsp) 13 activity and Nsp12-Nsp8-Nsp7 complex of SARS-CoV-2, which were essential for viral replication and transcription [ 43 , 44 ]. We reported the antiviral mechanism of CEP against GX_P2V appears to be associated with cell stress response-autophagy cascade, indicating that CEP exhibits broad-spectrum antiviral activity targeting multiple molecules and pathways.…”
Section: Discussionmentioning
confidence: 99%